Production and compositional studies of milk in local Pabna cows of Bangladesh - Talukder, Md Azharul Islam; Shahjahan, Md; Habib, Md Rezwanul; Salahuddin, Md; Rahman, Seikh Masudur; Ali, Md Yousuf; Munira, Sirazum; Miah, Md Abu Haris; Billah, Md Mostain; Rahman, Shahidur; Bhuiyan, Abul Kashem Fazlul Haque (Asian Journal of Medical and Biological Research, 2019)
The Pabna is one of the potential local cattle breeds in Bangladesh regarding milk production and its nutritive quality. The aim of the study was to know the effect of lactation length, parity and management on production performance and nutritional/physiochemical composition of the milk of local Pabna cows. Besides the regular milking, 15 days’ interval test day milking was recorded from 12 local Pabna cows with different lactation period (up to fifth month of calving) from BLRI Regional Station, Baghabari during January-September, 2018. In addition, 12 and 16 milk samples (200 ml/sample) were collected from the cows raised at BLRI Regional Station and the community of Dairy Development Research Project at Bera, Pabna district during June, 2018, respectively. Data were analyzed in an ANOVA of Completely Randomized Design and independent sample t-test, respectively, using SAS version 9.1.3 (SAS Institute Inc., Cary, NC, USA) including Tukey’s HSD post hoc test to separate means. The average daily milk yield was significantly (p<0.05) higher during the first month (4.62 L) of lactation and the lowest value recorded at 5th month (3.50 L). Among the test days milking better yield observed at 15 days (4.79 L) of experimental lactation period (p<0.05). The effect of lactation stages and parity number had no significant variations (p>0.05) on nutrient compositions of local Pabna cows’ milk in both on-station and community. However, the overall characteristics of milk between on-station and community had significant differences on the composition of total solids (p<0.001), SNF (p<0.001), fat (p<0.01), and protein (p<0.05) where the highest values found as 14.81, 8.65, 6.17 and 3.53% at on-station, respectively. The first month of lactation observed as best milk producing period among the five months and the management system had positive association with milk composition of local Pabna cows. Asian J. Med. Biol. Res. March 2019, 5(1): 48-51